Use of fresh autogenous vaginal tunic in the experimental lamellar keratoplasty in dogs (Canis familiaris, LINNAEUS, 1758) - Galera, Paula Diniz [UNESP]; LAUS, José Luiz [UNESP]; FERREIRA, Affonso Luiz (Universidade de São Paulo (USP), Faculdade de Medicina Veterinária e Zootecnia (FMVZ), 2000)
Empregou-se a túnica vaginal autógena, a fresco, na ceratoplastia lamelar em cães. Foram utilizados 14 cães, a serem avaliados nos períodos iniciais, intermediários e tardios. Fotofobia, blefarospasmo, descarga ocular, edema, neovascularização e pigmentação corneanas foram observados. Os resultados mostraram ser a técnica factível de utilização na reparação corneana após ceratectomias superficiais.

Autogenous vaginal tunics have been researched in lamellar keratoplasty in dogs using fresh autogenous grafts in the repair of superficial keratectomies. Fourteen dogs have been used for the evaluation at the early, intermediary and late postoperative periods. Photophobia, blepharospasm, ocular discharge, edema, neovascularization and pigmentation have been observed. The results have showed that the original procedure is useful for the repair of corneas after superficial keratectomies.
Emprego da túnica vaginal autógena, a fresco, em ceratoplastia lamelar experimental em cães (Canis familiaris, LINNAEUS, 1758)
Keywords: Córnea; Ceratoplastia; Túnica vaginal; Cães; Cornea; Keratoplasty; Tunica vaginalis; Dogs